2018
DOI: 10.1016/j.jot.2017.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of urinary C-terminal telopeptide of type II collagen as a biomarker in osteoarthritis diagnosis

Abstract: SummaryObjectiveThis study aims to discover that the urinary C-terminal telopeptide of type II collagen (uCTX-II) levels differ between osteoarthritis (OA) patients and healthy individuals (controls). According to this difference, we may conclude that uCTX-II can be a biomarker for OA diagnosis.MethodsWe searched MEDLINE and EMBASE databases updated to 2014 to find literature on OA biomarkers. We retrieved the publications that met the required criterion. Literature quality was assessed according to the Newcas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“…Furthermore, a moderate correlation was found between urinary CTX-II levels and KL grades (r = 0.405, p < 0.001) and the multiple linear regression analysis demonstrated that urinary CTX-II was independently associated with KL grades, suggesting that urinary CTX-II levels are increased in patients with an increased OA severity. Recent meta-analysis also revealed that urinary CTX-II levels were consistently increased in patients with severe knee OA on radiographic evaluation compared to that in those with mild knee OA [14,15,24]. Therefore, urinary CTX-II could be a useful tool for monitoring OA disease progression and treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a moderate correlation was found between urinary CTX-II levels and KL grades (r = 0.405, p < 0.001) and the multiple linear regression analysis demonstrated that urinary CTX-II was independently associated with KL grades, suggesting that urinary CTX-II levels are increased in patients with an increased OA severity. Recent meta-analysis also revealed that urinary CTX-II levels were consistently increased in patients with severe knee OA on radiographic evaluation compared to that in those with mild knee OA [14,15,24]. Therefore, urinary CTX-II could be a useful tool for monitoring OA disease progression and treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, recent meta-analyses showed the potential of using urinary CTX-II levels to distinguish between patients with knee OA from healthy controls. However, this diagnostic feature is not upheld in Asian populations, probably due to the small number of studies that were conducted in Asia [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Subchondral bone provides structural support and shock absorber for superficial articular cartilage and undergoes dynamic balance between modeling and remodeling in response to mechanical stress . The process of bone remodeling is regulated by osteoclast and osteoblast activity, and abnormal remodeling is believed to trigger the onset of OA . However, whether the degeneration in subchondral bone is the principal factor for LFJ OA and the source of LBP needs to be further explored.…”
mentioning
confidence: 99%
“…9,10 The process of bone remodeling is regulated by osteoclast and osteoblast activity, and abnormal remodeling is believed to trigger the onset of OA. 11,12 However, whether the degeneration in subchondral bone is the principal factor for LFJ OA and the source of LBP needs to be further explored. Furthermore, the specific mechanism involved in this disease progression and potential therapy remains to be further evaluated.…”
mentioning
confidence: 99%
“…All statistical analyses were performed using the Review Manager (RevMan) software [ 35 ]. Publication bias was assessed by Begg's test and Egger's test with the STATA software version 12.0 [ 36 ].…”
Section: Methodsmentioning
confidence: 99%